172 'NCHD'S UNDERSTANDING OF THE 'DYING WITH DIGNITY BILL". (18th November 2021) - Ahern, E; McGurk, C; Claffey, P
Abstract: Background: The Dying with Dignity Bill is potential legislation that would permit terminally ill people to avail of medical assistance to die in certain circumstances. It would give a medical practitioner the legal right to provide assistance to a qualifying person to end their life, thus changing the medical landscape as we know it. This project aimed to assess current understanding in non-consultant hospital doctors (NCHDs) of the Dying with Dignity Bill. Methods: An online survey was distributed to NCHD's across a range of disciplines to ascertain current knowledge of the Dying with Dignity Bill. Descriptive analysis of data was conducted on Excel. Results: The survey was completed by 80 NCHDs. Of respondents 67.5% (n = 54) of respondents had heard of the Bill and 32.5% (n = 26) of them knew what it was. The Bill had not been read by 88% (n = 71) of respondents. Fifty seven per cent (n = 46) did not understand what was entailed in the Bill. The majority agreed (61.3%; n = 49) that it would impact their work as a clinician. Some 70.1% (n = 56) agreed that legislation was needed in this area. The majority answered neutral (45%; n = 35) that their profession were consulted in the creation of the Bill. It is believed that the Bill will not require a vote however 48% (n = 37) believed it would. However, the majority (72.7%, n = 56) answered correctly that the Bill had not been enacted yet. This Bill does not define the length of a 'terminal illness' yet 36.8% (n = 28) believed it to be within six months. It also states that it is the practitioner's role to decide when somebody is palliative and only 54.5% (n = 42) knew this. Conclusion: The Dying with Dignity Bill is poorly understood by NCHDs, despite it potentially having an impact on the role of hospital doctors in Ireland. Discussion and involvement of NCHD's in the potential formation of this Bill is crucial.